GENERALIZED INFLOW PERFORMANCE RELATIONSHIP (IPR) FOR PERFORATED GAS WELLS - Cakra, Heru
In this study, dimensionless IPR for perforated gas welsl built in purpose to eliminate many related variable and eliminates the need for conventional multipoint test. A wide range of rock and fluid properties under stabilized flow are used in developing this dimensionless IPR. Rock, fluid, and system properties used in this study were reservoir pressure, reservoir temperature, gas specific gravity, reservoir permeability, formation thickness, perforation zone thickness, numbers of perforation, penetration length, and penetration radius. Variables of perforation were the key properties for developing dimensionless IPR for perforated gas wells.